Open Government Policies in Ibero-America. Exploring a Decade of Changes in the Context of the Open Government Partnership (2011-2021) - Ramírez-Alujas, Álvaro V. (Revista del CLAD Reforma y Democracia, 2022)
This paper aims to carry out an analysis and critical reflection on the progress of open government policies in Ibero-American members of the Open Government Partnership, exploring findings over a period of ten years. The methodology used consisted of collecting, exploring, systematizing, and analyzing 63 national open government action plans implemented by 18 Ibero-American countries; reviewing in detail a database of 1298 commitments between the years 2011 and 2021; and considering another 63 initiatives linked to 12 subnational action plans in 7 local governments in the region. The open government approach has been an important tool for the transformation of the Ibero-American public sector in the last decade, with the regulatory and technology use as key areas in the process, as well as the efforts to promote public integrity and the improvement of public services in the processes of co-creation and implementation of commitments to institutional openness in the comparative regional agenda. Open government is presented as the main axis in a transition towards a model of collaborative and smart governance of public affairs, which will allow an adequate response to the challenges of the 21st century. The main conclusions are that Open Government Partnership has been a platform that has contributed to institutionalizing openness processes in all Ibero-American countries, with visible results and impacts in various areas of public policy. However, on the path to the construction and implementation of an open State, a greater integration effort is required to generate broader and more sustainable strategies that promote capacity building, especially in the territorial space.